Kajian Teori Pemikiran Adam Smith dan Relevansinya terhadap Perekonomian Masa Kini - Astuti, Ajeng Windi; Hasibuan, Zakia Hasanah; Harefa, Wanda Nilam Sari Br.; Purba, Bonaraja (Ikatan Da'i Indonesia, 2024)
This research aims to find out how the theory of Adam Smith's thinking is still connected to current economic conditions. The discussion focuses on looking at how the era of globalization and the development of innovative technology today is still related to Adam Smith's theory of thought. So, based on the results of this research, it can be concluded that in the context of globalization, Adam Smith's thoughts remain relevant in several aspects of the modern economy. The free market concept emphasized by Smith, for example, is still the basis of the modern economic system, especially in free trade and investment across national borders.